COMPARATIVE ANALYSIS OF ROMANTIC POETRY IN ENGLISH AND RUSSIAN LITERATURE BASED ON J. BYRON AND M. LERMONTOV’S POETRY - Ruzibayeva Aziza Kahramanovna (Western European Studies, 2024)
This article presents a comparative analysis of Romantic poetry in English and Russian literature, focusing on the works of two prominent poets, Lord Byron and Mikhail Lermontov. By examining their poetic styles, themes, and influences, this study seeks to highlight the similarities and differences between Romantic poetry in these two cultural contexts. Through a detailed exploration of selected poems by Byron and Lermontov, this article aims to provide insights into how the Romantic movement manifested in both English and Russian poetry
Keywords: Romantic poetry; Lord Byron; Mikhail Lermontov; English literature